Systematic Evolution of 5g/6g Wireless Networks: A Review Standardization, Vision, Application, Security, Requirements, Propagation and Blockchain - Kaschel-Carcamo, H; Adasme-Soto, P; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2024)
This article presents the systematic evolution of 5G and 6 G wireless networks and the future projections to be considered to face the promising technological change in different sectors, given by the increased efficiency and security, presenting the versions of the different 3GPP reals with a deployment plan until 2028. It also presents the challenges and vision of future generations and typical applications of future 6G wireless networks, along with the above, the characteristics of the applications and international standardization bodies are indicated. Another point analyzed were the problems of radio wave propagation in the different deployment scenarios, whether indoors or outdoors. The problems of link blocking and coverage of telecommunication services for users were analyzed in the field, and the ITU-R P.1410 recommendation was presented, which provides propagation concepts and predictive coverage methods for networks operating between 3 and 60 GHz. Finally, the benefits and advantages of blockchain in 5G and 6G wireless networks are presented, as services dedicated to the management of digital documentation, as is the case of smart agriculture 5.0, smart health and banking entities, among others, which will revolutionize private companies in terms of reducing operating costs and a promising future is also foreseen with the Metaverse-6G, transforming communication, driving innovation in commerce and education to build a more inclusive and egalitarian digital world. © 2024 IEEE.